Hamman’s syndrome in a patient with uncontrolled type 1 diabetes mellitus: a case report - Asahi Ishihara; Katsuyuki Sagishima; Tadashi Ejima; Manami Kuwahara; Naoyuki Hirata (JA Clinical Reports)
Abstract Background Hamman’s syndrome is a clinical entity characterized by the spontaneous leakage of air into the mediastinum. We report a patient with Hamman’s syndrome associated with diabetes ketoacidosis (DKA). Case presentation A 20-year-old foreign technical intern visited to a hospital because of nausea and shortness of breath. He had been diagnosed with diabetes in his home country and had initiated insulin therapy; however, since arriving in Japan, he had not accessed any medical services. Computed tomography revealed pneumomediastinum, while laboratory tests showed marked hyperglycemia, metabolic acidosis, and a significantly elevated blood ketone level (15,044 µmol/L). The patient was diagnosed with Hamman’s syndrome associated with DKA. Upper gastrointestinal endoscopy showed no evidence of gastrointestinal perforation. Conservative intensive care, including insulin therapy and fluid resuscitation, resulted in clinical improvement. Conclusion This case highlights the importance of recognizing Hamman’s syndrome in DKA and the need for culturally competent care in international residents.